The Effect of the Normalization of UEA-Israel Bilateral Relationship on the Improvement of the Economies of the Both Countries In 2020-2022 - Marsha Niswah (Mediasi: Journal of International Relations, 2021)
Relations between the UAE and Israel have been frosty for decades, but in the 2010s, informal ties between the two countries improved greatly and began to engage in extensive informal cooperation based on their shared opposition to Iran's nuclear program and regional influence. In 2020, the UAE and Israel finally officially agreed to normalize bilateral relations as embodied in the Abraham Accords. The text of the UAE-Israel normalization agreement outlines several areas in which the country is trying to cooperate, including in several sectors of the economy. The purpose of this study is to determine the dynamics of normalizing bilateral relations and the influence of the normalization of bilateral relations between the UAE and Israel on increasing the economies of the two countries in 2020-2022. The method used in this study is a qualitative explanatory method. Data collection techniques were obtained by literature study, namely in the form of books, journals, and other literature related to this research. In addition, this study uses the concept of bilateral cooperation and the economic growth approach as a framework for economic analysis. The results of this study indicate that there has been an economic increase between the UAE and Israel after the normalization agreement in 2020 which will affect the normalization of bilateral relations between the UAE and Israel in 2021-2022.